Effects of large native herbivores on other animals. Issue 4 (22nd May 2014) - Foster, Claire N.; Barton, Philip S.; Lindenmayer, David B.; du Toit, Johan
Summary Large mammalian herbivores are major drivers of the structure and function of terrestrial ecosystems world‐wide, and changes in their abundance have resulted in many populations being actively managed. Many empirical studies have identified that abundant mammalian herbivores can have negative impacts on biodiversity, but there has been no specific review of the impacts of native mammalian herbivores. We assessed the peer‐reviewed literature on the effects of large native herbivores on other animals. We aimed to quantitatively synthesize current knowledge, identify gaps and limitations in the literature, and highlight priorities for future research. Most empirical studies of herbivory effects compared only two levels of herbivory (76%), and meta‐analysis showed that very high densities of herbivores, when compared with very low densities, had mostly negative effects on other animal species. These negative effects were usually attributed to changes in the quantity and/or structure of vegetation. Only 24% of papers studied animal responses across a gradient of herbivore densities, and nonlinear responses to herbivory, as well as responses to low and moderate herbivore densities, remain poorly understood. The literature also was dominated by short‐term studies (76% sampled animal responses for 2 years or less), and there was a high incidence of confounding factors among studies (38% of studies). In addition, many studies used only coarse metrics to assess effects (e.g. only 33% of studies assessed species composition) and few included community‐level synthesis (only 31% of studies reported results from more than one animal class). Synthesis and applications. Critical questions remain for both basic ecology and the management of large native herbivores for biodiversity. Key knowledge gaps include (i) nonlinear responses to herbivore pressure, (ii) how responses differ between different herbivores, (iii) the spatial and (iv) the temporal variation of responses, (v) how the effects of herbivores interact with other land management activities and (vi) the mechanisms driving cascading effects through ecosystems. We identify ways to address these gaps and emphasize the need for studies which employ contrasts over a gradient of ecologically relevant herbivore densities and biologically meaningful time frames.